Eze Goes to College With Moral Lessons - Nzekwu, Onuora and Crowder, Michael (Pilgrim Books Ltd, 1988)
When Eze wins a place at the college in Onitsha, everyone hopes he will do well. Are his adventures and his progress through his college years fascinating?...
Keywords: Juvenile Fiction / Adventure